LEARNING PAIN MANAGEMENT DURING CLINICAL MEDICAL EDUCATION: A CASE REPORT - Astrid Pratidina Susilo; Raden Besthadi Sukmono (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Heath professionals’ competence in the pain assessment and management is necessary to improve the quality of pain management. Evidence about pain learning in Indonesia is limited. Aims: This case report aimed to describe the learning and evaluation of 5th year medical student in a faculty of medicine in Indonesia on the pain assessment and management. The pain learning was introduced in a pre-internship module using lecture, case discussion, and the learning in the clinical rotation. Case discussion: PQRST mnemonic (Provoke and Palliate, Quality, Region and Radiation, Severity, Time) is introduced as a structure in the pain assessment. The OSCE showed that students need to improve the skills of communication and professionalism. Conclusion: PQRST mnemonic is beneficial to structure the pain assessment, but not enough to help students perform a holistic approach to the patient.